Estimation of the nuclear DNA content in some representative of genus Dioscorea - Obidiegwu, J.E.; Rodríguez, E.; Ene-Obong, E.E.; Loureiro, J.; Muoneke, C.O.; Santos, C.; Kolesnikova-Allen, M.; Asiedu, Robert (2009)
Nuclear DNA content of 54 accessions of 6 Dioscorea species collected from West African countries were determined using flow cytometry. Observed ploidy levels are diploid (2x), triploid (3x), tetraploid (4x), hexaploid (6x) and octoploid (8x). DNA index varied from 0.36 to 1.54 depending on the cultivar and considered specie. Estimated nuclear DNA sizes ranged from 0.702 ± 0.004 pg for G1 nuclei of diploid Dioscorea dumetorum to 2.573 ± 0.020 pg for G1 nuclei of octoploid Dioscorea cayenensis. Our result showed that there is a decrease in genome size with higher ploidy level. The study contributes a step towards a genome understanding of this group of plants